2019
DOI: 10.2807/1560-7917.es.2019.24.3.1800698
|View full text |Cite
|
Sign up to set email alerts
|

Detection of influenza A(H3N2) viruses exhibiting reduced susceptibility to the novel cap-dependent endonuclease inhibitor baloxavir in Japan, December 2018

Abstract: The novel cap-dependent endonuclease inhibitor baloxavir marboxil was approved for the treatment of influenza virus infection in Japan in February 2018. Two influenza A(H3N2) viruses carrying an I38T substitution in the polymerase acidic subunit (PA) were detected in baloxavir-treated children in December 2018. This mutation is known to confer reduced susceptibility to baloxavir, and the two mutant viruses exhibited 76- and 120-fold reduced susceptibility to baloxavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 5 publications
1
60
0
Order By: Relevance
“…Six to nine in vitro passages of A/WSN/33 (H1N1) virus in the presence of baloxavir revealed that an I38T substitution in PA conferred 22-to 41-fold reduced susceptibility to baloxavir . The PA I38T substitution occurs infrequently in naturally occurring A(H1N1)pdm09, A(H3N2), and B viruses (0%-0.02%) (Stevaert et al 2013;Takashita et al 2019b), suggesting that this substitution emerges as a result of treatment.…”
Section: Resistancementioning
confidence: 99%
“…Six to nine in vitro passages of A/WSN/33 (H1N1) virus in the presence of baloxavir revealed that an I38T substitution in PA conferred 22-to 41-fold reduced susceptibility to baloxavir . The PA I38T substitution occurs infrequently in naturally occurring A(H1N1)pdm09, A(H3N2), and B viruses (0%-0.02%) (Stevaert et al 2013;Takashita et al 2019b), suggesting that this substitution emerges as a result of treatment.…”
Section: Resistancementioning
confidence: 99%
“…Mutant viruses resistant to FAV are rarely isolated in vitro and in vivo with one exceptional case 3 . Although detection of viruses that exhibit reduced susceptibility to NA inhibitors or baloxavir marboxil in immunocompetent patients has frequently been reported 1,[4][5][6][7][8][9] , such viruses usually do not dominate susceptible viruses with the exception of the worldwide spread of oseltamivir-resistant H1N1 virus in the 2007-2008 season. Recently, broadly protective human monoclonal antibodies (mAbs) against conserved regions of HA, including the receptorbinding site (RBS) and stem region, have been evaluated [10][11][12][13][14][15][16] and studies for their clinical application are being conducted [17][18][19][20] .…”
mentioning
confidence: 99%
“…In the case of antivirals, their effectiveness is dependent on being administered within 48 h after appearance of symptoms [59, 60]. Importantly, antiviral-resistant strains have been described [1, 24–26]. Consequently, these prevention and treatment methods still leave substantial public health vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of antivirals, three major classes of drugs are FDA-approved for the treatment of influenza infections: NA inhibitors (oseltamivir, zanamivir and peramivir), matrix protein 2 (M2) inhibitors (amantadine and rimantadine), and the polymerase acid (PA) endonuclease inhibitor (Baloxavir marboxil or Xofluza) [1, 23]. However, influenza antiviral drugs have several limitations, including the lack of antiviral activity of M2 inhibitors against IBV, the emergence of drug resistant variants [24–26], and a limited antiviral effect due to rapid metabolism and elimination of the inhibitor [27–30]. Thus, there is an urgent need to find alternative approaches for the prevention and treatment of influenza infections in humans.…”
Section: Introductionmentioning
confidence: 99%